Manajemen Pengelolaan Kelas dalam Meningkatkan Interaksi Belajar Siswa Madrasah Ibtidaiyah Negeri Kota Bima - Trimansyah; Sa’adiah, Halimatus (Indonesian Journal of Islamic Elementary Education, 2024)
Good classroom management is one of the supporting factors for successful learning. This study aims to examine the implementation of classroom management in improving student learning interactions at the State Elementary School (MIN) in Bima City. This study is a qualitative study with a phenomenological approach. Data collection techniques were carried out by observation, interviews, and documentation. Data analysis was carried out by reducing data, presenting data, drawing conclusions, and verifying. The results of the study showed that classroom management at MIN Kota Bima was highly considered. The form of classroom management carried out at MIN Kota Bima is to organize students in the classroom to create and maintain student motivation so that they are always involved in the educational process at the madrasah. While the learning interaction that occurs is a reciprocal relationship between teachers and students, such as students being able to respond and respond quickly to the material taught by the teacher, students being able to ask questions without feeling awkward and inferior, and students being able to discuss well with their groups or deskmates. Supporting factors in classroom management and student learning interactions include learning motivation, ice breaking, teacher appreciation, learning media, and mastering teaching materials.